Produksi mutu benih beberapa varietas kedelai lokal Aceh (Glycine max (L.) Merr.) dengan pemberian dosis mikoriza yang berbeda pada tanah entisol - Putra, Rizki Ramadhana; Syafruddin, Syafruddin; Jumini, Jumini (-)
The aim of this study was to determine the effectof Aceh Soybean Local Varietiesand different doses of Mycorhiza on theproduction and seed quality, as well asthe interaction between both treatments. This research was conductedat the Experimental Farmof the Agriculture Faculty, Seed Scienceand Technology Laboratory and Plant Pathology Laboratory ofthe Agriculture Faculty, Syiah Kuala University from December2013 to March 2014 by using randomized block design (RBD) factorial with two treatments, the first treatment was varieties with three different varieties namely Bener Meriah, Kipas Merah and Anjasmoro, the second treatment wasdose ofmycorrhizal with four levels namely 0, 5, 10 and 15g/plant with three replications. The observed parameters were the number of pods/plant, number of podspithy/plant, number ofseeds/plant, seed weight/plant, weight of100 seeds, the potential of yieldper hectare, growth potential, seed germination, growth speed, growth simultaneity and weight of drynormal seedling.The results showedthat theKipas Merah varieties showed better results, but for the seed quality, Bener Meriah varieties show edbetter results. Whit the use ofmycorrhiza, dose of 10g/plant showed ``better resultson the root infection percentage parameters, while the other parameters, mycorrhiza doses howed nosignificant effect. Significant interaction between both factors iscontained in Anjas moro varieties with 5 g/plant mycorrhizal dose on the parameter rnumber of pods, seed weight, 100-seed weight and yield potentialper hectare, root infection percentage and growth simultaneity.